Albumin-Bound Paclitaxel: Worthy of Further Study in Sarcomas - Tian, Zhichao; Yao, Weitao (Frontiers in Oncology, 2022)
Taxanes (paclitaxel and docetaxel) play an important role in the treatment of advanced sarcomas. Albumin-bound paclitaxel (nab-paclitaxel) is a new kind of taxane and has many advantages compared with paclitaxel and docetaxel. Nab-paclitaxel is currently approved for the treatment of advanced breast, non-small cell lung, and pancreatic cancers. However, the efficacy of nab-paclitaxel in sarcomas has not been reviewed. In this review, we first compare the similarities and differences among nab-paclitaxel, paclitaxel, and docetaxel and then summarize the efficacy of nab-paclitaxel against various non-sarcoma malignancies based on clinical trials with reported results. The efficacy and clinical research progress on nab-paclitaxel in sarcomas are also summarized. This review will serve as a good reference for the application of nab-paclitaxel in clinical sarcoma treatment studies and the design of clinical trials.